Weight-bearing MRI of the knee: a review of advantages and limits - Bruno, Federico; Barile, Antonio; Arrigoni, Francesco; Laporta, Antonella; Russo, Anna; Carotti, Marina; Splendiani, Alessandra; Di Cesare, Ernesto; Masciocchi, Carlo (Acta Biomedica Atenei Parmensis, 2018)
Standard knee imaging with MRI is usually performed with patient in recumbent position under non-weight-bearing conditions. Recently, magnetic resonance imaging systems to scan the knee joint under weight bearing conditions has been proposed as an approach to improve the clinical utility of musculoskeletal MRI. Imaging under loading can be useful to understand the natural motion behavior of the knee joint and to identify conditions that are challenging to diagnose by using standard position. We reviewed the literature on weight-bearing MR imaging of the knee to describe the current state of use of such MRI technologies, evaluating the advantages and the potential limitations of these technologies.